Development of an IoT Based on Solar Tracking System - Hairil, Irfan Nur Hafiy; Binti Mohd Nor, Faridah Hanim (Progress in Engineering Application and Technology, 2024)
Solar energy, a renewable resource with significant potential, encounters challenges in attaining optimal utilization, particularly in static solar systems where energy production can be limited by less-than-optimal alignment with the sun’s position during the day. To obtain the desired outcomes, a system employing detectors is necessary. This system utilizes an ESP32 microcontroller to regulate the movement of the panels and display the solar input production of the panels. The selection of this tracking system was based on its superior accuracy in capturing the highest possible amount of solar energy. The objective of this technology is to enhance the efficiency of energy acquisition by aligning the solar panels with the path of the sun. The objective of the research is to assess the system’s performance in relation to a stationary system, with the goal of quantifying the enhancement in energy generation achieved by implementing continuous sun monitoring. The results indicate a substantial rise of up to 25% in energy generation compared to a fixed system. This enhancement pertains to the tracking system’s consistent capability to align with the sun’s position, guaranteeing optimal performance. This study highlights the ability of solar tracking technology to enhance the utilization of renewable energy and promote the progress of sustainable energy solutions.